Inovasi wisata edukasi Ciletuh Unesco Global Geopark melalui produk hanjeli E-Dye - Cucu Ruhidawati; Winwin Wiana; Katiah Katiah; Pipin Tresna; Feny Puspitasari (Jurnal Abmas, 2023)
The tourist village, which has the potential to attract people to visit and travel, requires innovation by utilizing the existing local potential. The development of the Ciletuh tourism village area is an effort to improve and develop the natural potential of Hanjeli villages around Ciletuh Unesco Global Geopark, with a strategy to introduce the abundant natural potential and process it into a characteristic of the Ciletuh tourism village. Hanjeli is a superior Waluran Mandiri Tourism Village product, but has not been optimally utilized as a creative product in other fields besides food. Based on this, the methodology of community service carried out by the academic community of the Fashion Education study program in solving problems is using Action research. Action Research from community service involving targets between PKK cadres and direct targets of the community / young women, as many as 20 people in Waluran Village in the Ciletuh Tourism Village Area. The results of the Action are the existence of products other than food and strategies to explore the potential of hanjeli by applying ecoprint-tie dye techniques that produce attractive textile motifs, are environmentally friendly and are a fashion trend that is very popular with the public, especially the younger generation or visitors to the Ciletuh tourist village.   Abstrak Desa wisata sebagai desa yang memiliki potensi yang dapat menggerakkan orang orang untuk berkunjung dengan tujuan berwisata membutuhkan inovasi dengan memanfaatkan potensi lokal yang diunggulkan. Pengembangan kawasan desa wisata Ciletuh sebagai upaya untuk meningkatkan dan mengembangkan potensi alam hanjeli desa sekitar Ciletuh Unesco Global Geopark dengan strategi mengenalkan potensi alam yang melimpah dan dapat diolah menjadi ciri khas desa wisata Ciletuh. Hanjeli merupakan produk unggulan Desa Wisata Waluran Mandiri tetapi belum dimanfaatkan dengan optimal sebagai produk kreatif di bidang lain selain pangan. Berdasarkan hal tersebut metodologi pengabdian kepada masyarakat yang dilakukan oleh sivitas akademika prodi Pendidikan tata busana di dalam memecahkan permasalahan adalah menggunakan Action research. Action Research dari pengabdian kepada masyarakat yang melibatkan sasaran antara kader PKK dan sasaran langsung masyarakat/ perempuan muda sebanyak 20 orang di Desa Waluran di Kawasan Desa Wisata Ciletuh. Hasil dari Action adalah terdapatnya produk selain makanan dan strategi untuk mengeksplorasi potensi hanjeli dengan diterapkan teknik ecoprint-tie dye yang menghasilkan motif tekstil yang menarik, ramah lingkungan dan merupakan tren fesyen yang sangat digemari masyarakat, terutama generasi muda atau pengunjung desa wisata Ciletuh. Kata Kunci: desa wisata Ciletuh; ecoprint; hanjeli; teknik tie dye